Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Wayground Paper Mode dalam Meningkatkan Hasil Belajar IPAS Siswa Kelas V SDN 28 Cakranegara - Elindaria Dwi Kencana; Muhammad Erfan; Nurwahidah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Wayground Paper Mode on improving the science and social studies (IPAS) learning outcomes of fifth-grade students at 28th Cakranegara State Elementary School in the 2025/2026 academic year. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of all fifth-grade students at 28th Cakranegara State Elementary School. The sample was selected using a saturated sampling technique, with Class VA serving as the experimental group and Class VB as the control group. The research instrument was a learning outcomes test in the form of multiple-choice questions that measured the cognitive indicators of remembering, understanding, applying, and analyzing. Data were collected through tests and observations. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s Test of homogeneity, the Independent Samples t-Test for hypothesis testing, and the N-Gain test with the assistance of IBM SPSS Statistics 25.The results of the hypothesis test showed a significance value of 0.001 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. In addition, the mean posttest score of the experimental group was 83.48, which was higher than that of the control group at 73.00. These findings indicate that the use of the TGT cooperative learning model assisted by Wayground Paper Mode had a significant effect on the IPAS learning outcomes of fifth-grade students at 28th Cakranegara State Elementary School.